Influence of Silica/Sulfonated Polyether-Ether Ketone as Polymer Electrolyte Membrane for Hydrogen Fueled Proton Exchange Membrane Fuel Cells - Sri Handayani; Eniya Listiani Dewi Listiani Dewi (International Journal of Science and Engineering, 2011)
The operation of non-humidified condition of proton exchange membrane fuel cell (PEMFC) using composite sPEEK-silica membrane is reported. Sulfonated membrane of PEEK is known as hydrocarbon polyelectrolyte membrane for PEMFC and direct methanol fuel cell (DMFC). The state of the art of fuel cells is based on the perluorosulfonic acid membrane (Nafion). Nafion has been the most used in both PEMFC and DMFC due to good performance although in low humidified condition showed poor current density. Here we reported the effect of silica in hydrocarbon sPEEK membrane that contributes for a better water management system inside the cell, and showed 0.16 W/cm2 of power density which is 78% higher than that of non-silica modified [Keywords: composite membrane, polyether-ether ketone, silica, proton exchange membrane fuel cell].